Tailored therapy guided by genotypic resistance from gastric mucosa samples in the first-line treatment of infection: a systematic review and meta-analysis - Cailing Li; Kai Zhou; Baojun Suo; Yanyan Shi; Guangjie Ping; Liya Zhou; Zhiqiang Song (Therapeutic Advances in Gastroenterology)
Background: Tailored therapy is crucial for reducing the irrational use of antibiotics and enhancing Helicobacter pylori ( H. pylori ) eradication rates. Detection of antibiotic resistance gene mutations offers a rapid, accurate, and simple approach for tailored therapy, facilitating its widespread clinical implementation. However, the efficacy, safety, adherence, and cost-effectiveness of tailored therapy guided by genotypic resistance from gastric mucosa samples for first-line H. pylori treatment remain unclear. Objectives: This study aims to clarify the efficacy, safety, patient compliance, and cost-effectiveness of genotypic resistance-guided tailored therapy for first-line H. pylori treatment. Design: A systematic review and meta-analysis following the PRISMA 2020 guidelines. Data sources and methods: The literature was searched in PubMed, Web of Science, and Wanfang databases under the keywords “ Helicobacter pylori ,” “tailored therapy,” and “genotypic resistance” before March 1, 2025. Two investigators independently performed data extraction and literature quality assessment. Single-arm meta-analysis was performed using the Meta package of the R program to summarize the efficacy, safety, and compliance of tailored therapy, and classical meta-analysis was performed using Review Manager to compare tailored therapy with empirical treatment. Dichotomous outcomes were summarized using relative risks with 95% confidence intervals. Results: Of 1524 retrieved articles, 29 (including 4895 patients) met inclusion criteria for single-arm meta-analysis, and 17 (including 6208 patients) were included in the classical meta-analysis by further excluding studies that did not use empirical treatment as control. The single-arm meta-analysis demonstrated satisfactory efficacy of tailored therapy in first-line H. pylori treatment (intention-to-treat analysis: 84.4%, per-protocol analysis: 91.7%), with good safety (adverse event rate: 26.6%) and adherence (98.0%). Tailored therapy showed a higher overall eradication rate than empirical treatment. Subgroup analysis indicated that tailored therapy outperformed standard triple therapy and was comparable to bismuth quadruple therapy and concomitant therapy in terms of efficacy, with similar safety and adherence across groups. Health economic evidence was limited, but most studies suggested that tailored therapy incurred higher costs per successful eradication than empirical treatment. Conclusion: Tailored therapy guided by genotypic resistance detected from gastric mucosa samples demonstrates satisfactory eradication efficacy in first-line H. pylori treatment, superior to standard triple therapy and comparable to bismuth quadruple therapy, with comparable safety and adherence. Current evidence supports bismuth quadruple therapy as the optimal first-line treatment for H. pylori infection. Considering factors such as cost-effectiveness and technical accessibility, it is more appropriate to implement tailored therapy in countries and regions with adequate resources and capabilities. Trial registration: This study was not registered in PROSPERO, and future systematic reviews and meta-analyses will be registered in advance.